Báo cáo Giải trình, tiếp thu, chỉnh lý dự thảo Luật Đấu thầu (sửa đổi) (kèm theo Báo cáo tóm tắt) - Uỷ ban Thường vụ Quốc hội (2023)
Toàn văn Báo cáo Giải trình, tiếp thu, chỉnh lý dự thảo Luật Đấu thầu (sửa đổi) (kèm theo Báo cáo tóm tắt).